Challenges facing the implementation of quality control by radiographers in Tanzania - Wilson Maliyatabu Ngoye; Jenny Motto; Wilbroad Edward Muhogora (Brazilian Journal of Radiation Sciences)
Quality control (QC) programme is vital for quality radiological services at low radiation dose and costs. However, the QC implementation by radiographers in Tanzania is inadequate. This study aimed at investigating the challenges facing the implementation of the QC programme by radiographers in diagnostic radiography units in Tanzania and recommend strategies to mitigate the challenges. The study was conducted on a sample of 84 radiographers who have been trained on the QC programme, and who were practicing in 54 hospitals within Tanzania. Majority of respondents agreed that the lack of standardized test tools (98.8%) and lack of managerial support (51.8%) were hindering the QC programme. Also, the lack of care of equipment by radiographers and lack of motivation were identified. The strategies suggested to improve the programme include more enforcement (63.9%), assistance by the government (44.6%), motivation (33.7%) and improvement of the QC training (32.5%). Also, professional development activities and QC awareness to hospital management teams were suggested. It is crucial that the barriers to the QC programme are addressed and the strategies identified are considered if comprehensive implementation of the QC programme is to be realized.